Helpless within borders: the case of adequate international human rights protection for IDPs in Northern Uganda and the Darfur region of Sudan - Harrell-Bond, Barbara (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.